Analysis of Factors Affecting Employee Performance at Palm Oil Company PT. Betami Aceh Tamiang - Helvy Ramadhani; Amalia Harmin (Fakultas Teknik Universitas Samudra, 2024)
Aceh Province is an area rich in natural resources for oil palm plantations, which can be optimized. Many oil palm companies are established in Aceh. PT Betami, as one of the many Palm Oil Plantation companies in Aceh Tamiang, must improve the performance of its employees in order to compete with competitors. This research aims to describe the factors that can influence employee performance at PT Betami, describe the performance of PT Betami employees, and analyze the influence of salary, incentives, motivation, work environment, training, and development on the performance of PT Betami employees. The research was conducted at the PT Betami Palm Oil Company on Jln. Sapta Jaya, Suka Jadi Village, Rantau District, Aceh Tamiang Regency. The research method used is a survey using observation and questionnaires. The research sample was 77 people and was calculated using the Slovin formula. Sampling was carried out using the Simple Random Sampling technique. Data analysis was done using descriptive and multiple linear regression analyses using SPSS. The research results show that the performance of PT Betami employees is excellent. Salary, incentives, motivation, work environment, training, and development can influence PT Betami employees' performance. Motivation and incentives can influence employee performance in the highest category.